Effects of Structural Dynamic Characteristics on Soil–Structure Interaction (SSI) Analysis of High-Frequency-Dominant Seismic Excitation - Huina Jang; Jaeyong Yoon; Wanjei Cho; Jungwhee Lee (Applied Sciences)
This study investigates how structural dynamic characteristics affect the response to high-frequency dominant seismic excitations, using a 3D numerical analysis considering soil–structure interaction (SSI). For this purpose, an SSI analysis was conducted using the finite element analysis software LS-DYNA, incorporating four representative Korean geotechnical characteristics and the 2016 Gyeongju earthquake, characterized by dominant high-frequency components. A comparison was conducted between a fixed-end model without considering SSI and an embedded model with SSI for a high-rise structure (40 stories) with low natural frequencies, and a low-rise structure (5 stories) with high natural frequencies. The analysis focused on key dynamic responses, including the natural frequency, frequency of maximum response, and maximum relative displacement of the structures, to identify differences in the SSI effect based on the structures’ dynamic characteristics and the soil types. The analysis generally revealed that the SSI effect lowers the natural frequencies of structures and increases the damping effect. It was also found that depending on the match between the dominant frequency range of the seismic excitations and the range of the structure’s natural frequencies, larger dynamic responses were calculated when SSI was considered, suggesting that it may be necessary to consider SSI for conservative design results.